Comparative Study between High Resolution Ultrasound and MRI in Diagnosis of Rotator Cuff Tears - Alsayed Abdelhameed Ahmed; Ghada M. Abdelraziq; Khaled Hassan Mosallam; Heba Hassan Ahmed (SVU - International Journal of Medical Sciences, 2023)
Background: The four muscles that support the humeral head and come from the anterior and posterior sides of the scapula with their tendons situated in the smaller and larger tuberosities are collectively known as the "rotator cuff." The teres minor, supraspinatus, infraspinatus, and subscapularis are among these muscles. Objectives: This study compares dynamic high-resolution ultrasonography to MRI, which was the gold standard to assess the value of each technology in identifying rotator cuff injury. Patients and methods: This was prospective study for fifty patients were sent to the Diagnostic and Interventional Radiology Clinic in Qena City suspected to have rotator cuff injury. . Results: Patients' ages ranged from 19 to 70, with a mean age of 36 years, a standard deviation of 16.35 years. In our study, there were a total of 32 affected males (64%) and 18 affected females (36%) with a male to female ratio of 1.78:1. In identifying complete tears in our patients, in general, we found that USG has 100% overall sensitivity, 92.68% overall specificity, and 94% overall diagnostic accuracy. Positive predictive value was 75%, whereas the negative predictive value was 100%. Conclusion: MRI and ultrasound have similar levels of sensitivity and specificity. When high-resolution imaging is feasible, trained radiologists are on hand, and rotator cuff integrity is the main concern, US may be thought of as the screening method because it is less expensive and more widely available.